'Living in a Zoom world': Survey mapping how COVID‐19 is changing family therapy practice in the UK. Issue 2 (11th February 2021) - Mc Kenny, Richard; Galloghly, Emily; Porter, Catherine M.; Burbach, Frank R.
Abstract : Following the COVID‐19 pandemic, psychological therapies rapidly moved online in mid‐2020. The Association for Family Therapy and Systemic Practice in the UK (AFT) surveyed the attitudes and practices of systemic therapists in the UK in early October 2020, exploring members' views and gathered information about ongoing needs. A sample of 312 people were included in a mixed methods analysis. In total, 65% of respondents felt their overall experience of using online video technology professionally was positive, further reflected in responses to two open‐ended questions. Detailed thematic analysis revealed that many positive comments were related to the practical advantages of online working, whilst many negative comments were related to technique and the therapeutic relationship. Possible respondent biases are discussed, and the implications of this change in practice are explored. It remains to be seen if this marks the beginning of a more permanent shift in our field as we explore the potential of new technologies. Practitioner Points: The vast majority of UK systemic therapists felt that their experience of online video technology was positive. They noted many practical advantages but also identified many challenges regarding therapeutic techniques and the therapeutic relationship. Therapists developed a range of creative solutions to maximise the therapeutic opportunities of online video. Abstract : 在新冠肺炎大流行之后，心理治疗迅速在2020年中期转到线上。英国家庭治疗和系统实践协会（AFT）于2020年10月初对英国系统治疗师的态度和实践进行了调查，探讨了成员的观点，并收集了有关持续存在的需求的信息。采用混合方法分析了312个样本。65%的受访者认为他们在工作中使用在线视频技术的总体体验是积极的，这进一步反映在对两个开放式问题的回答中。详细的主题分析显示，许多正面评论与线上工作的实际优势有关，而许多负面评论与技术和治疗关系有关。本文讨论了受访者可能存在的偏见，并探讨了实践当中这种变化的含义。在我们探索新技术的潜力时，这是否标志着我们的领域开始了一个更持久的转变，还有待观察。 对从业者的启示: 绝大多数英国系统治疗师认为他们线上视频技术的体验是积极的 他们指出了许多实际优势，但也指出了在治疗技术和治疗关系方面的许多挑战 治疗师开发了一系列创造性的解决方案，以最大限度地利用线上视频的治疗机会 Abstract : Después de la pandemia de COVID‐19, las terapias psicológicas se cambiaron rápidamente a formato online a mediados de 2020. La Asociación para la Terapia Familiar y la Práctica Sistémica en el Reino Unido (AFT) encuestó las actitudes y prácticas de los terapeutas sistémicos en el Reino Unido a principios de octubre de 2020, explorando las opiniones de los miembros y recopilado información sobre las necesidades actuales. Se incluyó una muestra de 312 en un análisis de métodos mixtos. El 65% de los encuestados sintió que su experiencia general de uso profesional de la tecnología de video en línea fue positiva, lo que se refleja en las respuestas a dos preguntas abiertas. El análisis temático detallado reveló que muchos comentarios positivos se relacionaban con las ventajas prácticas del trabajo en línea, mientras que muchos comentarios negativos se relacionaban con la técnica y la relación terapéutica. Se discuten los posibles sesgos de los encuestados y se exploran las implicaciones de este cambio en la práctica. Queda por ver si esto marca el comienzo de un cambio más permanente en nuestro campo a medida que exploramos el potencial de las nuevas tecnologías. Puntos de implicación práctica: La gran mayoría de terapeutas sistémicos del Reino Unido consideró que su experiencia con la tecnología de video online fue positiva Notaron muchas ventajas prácticas pero también identificaron muchos desafíos con respecto a las técnicas terapéuticas y la relación terapéutica Los terapeutas desarrollaron una gama de soluciones creativas para maximizar las oportunidades terapéuticas del video en línea.